Analisis Rekrutment dan Penempatan Kerja pada Kinerja Karyawan Perusahaan Trans Berjaya - Sri Mulyeni; Santi Santi; Lien Nurliah; Imas Siti Masitoh; Hanifah Sukmana; Sobarna Kartamihardja (Universitas 17 Agustus 1945 Semarang, 2023)
The research explains the relationship between employee recruitment and work placement on employee performance at CV Trans Berjaya, the research sample used is a saturated sample because population under 100. The research instrument used a questionnaire, tested data through partial and simultaneous tests, multiple regression test using SPSS 25 software. Partial test results revealed that variabel X1 recruitment affected employee performance by 0,722 or 72,2% and variable X2 work placement influenced performance employees by 0,631 0r 63,1%. And the simultaneous test of recruitment and work placement variables on employee performance has an impact of 0,731 or 73,1%. Thus, the performance of Trans Berjaya employees is influenced by recruitment and job placement. Variables X1 and X2 have a positive and significant effect variable Y.